2001
DOI: 10.2741/hansen
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and cancer: effects of 1,25(OH)2D3 and its analogs on growth control and tumorigenesis

Abstract: Today, it is well established that besides playing a crucial role in the establishment and maintenance of the calcium homeostasis in the body, the active form of vitamin D, 1,25(OH)2D3, also acts an effective regulator of cell growth and differentiation in a number of different cell types, including cancer cells. This has led to an increased interest in using 1,25(OH)2D3 in the treatment or prevention of cancer patients and to a substantial number of studies investigating the effect of 1,25(OH)2D3 on cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
119
0
4

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 227 publications
(154 reference statements)
1
119
0
4
Order By: Relevance
“…the bcl-2 family, insulin-like growth factor I/II, and tumor necrosis factor-alpha. 2,31,32 As these general mechanisms of cellular growth equally apply to premenopausal and postmenopausal women, a protective effect of vitamin D on both premenopausal and postmenopausal breast cancer is likely.…”
Section: Discussionmentioning
confidence: 99%
“…the bcl-2 family, insulin-like growth factor I/II, and tumor necrosis factor-alpha. 2,31,32 As these general mechanisms of cellular growth equally apply to premenopausal and postmenopausal women, a protective effect of vitamin D on both premenopausal and postmenopausal breast cancer is likely.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the established role of vitamin D 3 in the regulation of calcium homeostasis, numerous studies have shown the metabolically active form of vitamin D 3 , 1,25-dihydroxyvitamin D 3 [1,25(OH) 2 D 3 ], to have strong growth-inhibitory effects on a variety of tumor cell lines (1). Because hypercalcemia limits the concentrations of vitamin D 3 achievable in the clinic, several vitamin D 3 analogues, such as EB 1089 (seocalcitol), have been synthesized with reduced hypercalcemic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work from this laboratory has shown that vitamin D 3 [1,25(OH) 2 D 3 ; cholecalciferol] and vitamin D 3 analogues, such as EB 1089 and ILX23-7553, enhance the response to both ionizing radiation (IR) and the antitumor drug, Adriamycin, in breast tumor cells (2 -5); for IR, the effects of EB 1089 were also shown to occur in tumor cell xenografts (6). These findings are consistent with previous work by several research groups showing that vitamin D 3 and/or its analogues can potentiate the sensitivity to chemotherapeutic drugs in various experimental tumor systems (7 -12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, many synthetic analogues of 1,25(OH) 2 D 3 have been developed with the goal of developing analogues that exhibit similar or enhanced growth-inhibitory and antimetastatic properties with reduced calcaemic effects (Schwartz and Hulka, 1990) (see also Hansen et al (2001) (Chen et al, 2000).…”
mentioning
confidence: 99%